2017
DOI: 10.1248/bpb.b17-00307
|View full text |Cite
|
Sign up to set email alerts
|

FOXA1 Induces E-Cadherin Expression at the Protein Level <i>via</i> Suppression of Slug in Epithelial Breast Cancer Cells

Abstract: Epithelial-to-mesenchymal transition (EMT) is an important process during embryonic development and tumor progression by which adherent epithelial cells acquire mesenchymal properties. Forkhead box protein A1 (FOXA1) is a transcriptional regulator preferentially expressed in epithelial breast cancer cells, and its expression is lost in mesenchymal breast cancer cells. However, the implication of this biased expression of FOXA1 in breast cancer is not fully understood. In this study, we analyzed the involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Our data showed that the expression of FOXA1 correlated positively with E-cadherin which is in line with previous reports [39,40]. Anzai et al reported that FOXA1 promotes E-cadherin expression at the protein level by suppressing Slug expression in MCF7 cells [41]. Similarly, in gastric cancer cells, FOXA1 regulates the EMT in cancer cells, by inducing the E-cadherin expression and decreasing the vimentin protein level [42].…”
Section: Biomed Research Internationalsupporting
confidence: 92%
“…Our data showed that the expression of FOXA1 correlated positively with E-cadherin which is in line with previous reports [39,40]. Anzai et al reported that FOXA1 promotes E-cadherin expression at the protein level by suppressing Slug expression in MCF7 cells [41]. Similarly, in gastric cancer cells, FOXA1 regulates the EMT in cancer cells, by inducing the E-cadherin expression and decreasing the vimentin protein level [42].…”
Section: Biomed Research Internationalsupporting
confidence: 92%
“…STAT3 is reported to increase invasion and metastasis by inducing matrix metalloproteinase (MMP) expression [22]. STAT3 can also bind to an antisilencer element in the VIMENTIN promoter to enhance VIMENTIN gene expression and can directly or indirectly target certain transcriptional regulators of E-CADHERIN, such as HIF-1 and SLUG, to regulate EMT progression in cancer [20,21]. Consistent with the above findings, we found that the levels of JAK2, p-JAK2 (Tyr1007/1008), and p-STAT3 (Tyr705) were upregulated in REX1-overexpressing cervical cancer cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, these classical EMT-related genes are downstream targets of the JAK2/STAT3-signaling pathway, which is negatively regulated by the SOCS family [20][21][22][23][24][25][26][27]. Therefore, we investigated the expression of the key proteins of the JAK2/STAT3 pathway in the present study.…”
Section: Rex1 Activates the Jak2/stat3 Pathway By Downregulating Socsmentioning
confidence: 99%
“…In MDA-MB-231 cells, Snail was necessary for binding of Slug to the ZEB1 promoter and its activation indicating that Slug alone may not drive EMT in the absence of Snail (Ye et al, 2015 ). On the other hand, Slug can attenuate E-cadherin levels indirectly by post-transcriptional mechanisms through miR-221 and by promoting protein degradation (Pan et al, 2016 ; Anzai et al, 2017 ). Using oncogene-transformed human mammary epithelial cells (HMLER), Kroger et al showed that Slug protein expression in such epithelial cells was similar to that in mesenchymal and hybrid E/M cells.…”
Section: Slug and Emt: Guilty By Association?mentioning
confidence: 99%